ANALISIS PENGARUH KEMISKINAN, PENGANGGURAN, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Nairizi, Mirza Ahmad (Jendela Inovasi Daerah, 2023)
This study aims to analyze the effect of poverty, unemployment and inflation on Indonesia's economic growth. The data used is time series data from 1991 to 2020 on an annual basis. Data were analyzed using the ECM (Error Correction Model) method with the help of Eviews 10. The results showed that the variables of unemployment and inflation in the short and long term did not have a significant effect on economic growth. Meanwhile, the poverty variable in the short term and long term has a significant influence on economic growth. The research results show that poverty is a macroeconomic variable that plays a major role in hindering economic growth in Indonesia.